The relationship between urbanization, energy use and carbon emissions: evidence from a panel of Association of Southeast Asian Nations (ASEAN) countries - Wang, Yuan; Chen, Lili; Kubota, Jumpei (Journal of cleaner production, 2016)
This study uses annual data to detect the nexus between urbanization, energy use, and carbon emissions in a panel of Association of Southeast Asian Nations (ASEAN) countries spanning the period 1980–2009. The study contributes to the increasing empirical literature by investigating the effects of urbanization and detecting causal links between the variables. Results from the Pedroni panel cointegration tests show evidence for the existence of a long-term equilibrium relationship between urbanization, energy use, and carbon emissions for the ASEAN countries. Using the panel fully modified ordinary least squares technique, the effect of urbanization on carbon emissions is further revealed; i.e., a 1% rise in urban population results in a 0.20% increase in carbon emissions. Unilateral short-run causal relationships from urbanization to energy use and from urbanization to carbon emissions have been found by Granger causality tests. Also, the results clearly indicate that in the long term, urbanization together with energy use Granger causes carbon emissions. The paper concludes with main findings and provides recommendations toward rational planning of urban development and energy-efficiency improvement strategies for the ASEAN countries. •Panel causality between urbanization, energy and CO2 is performed for the ASEAN.•Short- and long-run causalities from urbanization to carbon emissions are present.•Urbanization together with energy use induces the increase of carbon emissions.